Preferences of muslim consumers towards takaful among Shah Alam populations / Mohammad Noor Faiz Mohd Zin - Mohd Zin, Mohammad Noor Faiz (2019)
The word Takaful is derived from the Arabic verb 'Kafala', which means to guarantee, looking after, to help and to take of one's needs. Takaful is a system of Islamic insurance based on the principle of 'ta'awun' (mutual assistance) and 'tabarru' (voluntary contribution). Lack of knowledge and awareness among the people has caused the Islamic financial system such as the Takaful industry to be slower as compared to the conventional insurance system. The contribution in the Takaful is very important things as a Muslim which is in fulfilling a religious obligation and for the financial protection to their life insurance. The lack of knowledge and understanding cannot be solved simply by only urged the participants in contributing their wealth without giving them a better understanding of Takaful. It is very vital to ensure the society have a clear understanding about Takaful which can be influencing them to make the contribution as a participant for their financial protections in life insurance. This research aim is to identify the level of knowledge within their awareness, the level acceptance among the society, the perception of Muslim consumers towards Takaful and also to analyse the factors influencing the consumers to involve in Takaful. This research is based on the data obtained from a survey questionnaire that polled Muslim consumer's perception towards Takaful system. Data were processed and analysed using SPSS software version 2.0. The researcher was found out there is a strong correlation between independent variables and Muslim consumer's perception regarding the nomination of Takaful. This study also found that the mean score for acceptance, knowledge, awareness, and factors that influence the Muslim consumer's to make a contribution in Takaful as their financial protection. The mean score for an objective of this study shows the level of acceptance between medium-high and high. It is hoped this study can contribute to an improvement of Islamic insurance system as we call as Takaful to encourage more participants to make the contribution in Takaful industry.